Development and Validation of IHES Measuring ICT Integration among Faculty Members in Indian Higher Education Sector - Singh, Bushra S. P.; Malhotra, Meenakshi (Gyan Management Journal, 2018)
Students are the key to tomorrow’s success and are the future. Technology has been instrumental in bringing about a muchneeded change in the way students learn in classrooms, libraries or at home. It is imperative that the potential of technology in revolutionizing pedagogy be realized and exploited to the greatest extent possible. Nowadays, governments are aiming to achieve digital literacy and ICT proficiency. Digital literacy is "comprises a set of basic skills which include the use and production of digital media, information processing and retrieval, participation in social networks for creation and sharing of knowledge, and a wide range of professional computing skills" (UNESCO Institute for Information Technologies in Education, 2011). ICT proficiency is "the ability to use digital technology, communication tools, and/or networks appropriately to solve information problems in order to function in an information society. This includes the ability to use technology as a tool to research, organize, evaluate, and communicate information and the possession of a fundamental understanding of the ethical/legal issues surrounding the access and use of information" (International ICT Literacy Panel, 2002).